Meningkatkan Kemampuan Kognitif Anak Usia 4-5 Tahun Melalui Ketrampilan Mengurutkan Pola Dengan Media Loose Part Di Tk Al-Iman Surabaya - istiqomah, nurul; Sari, Anisa Yunita (MOTORIC, 2024)
Sorting patterns according to Polonsky and Dorothy is the ability to sort a set of objects that are interconnected with one another. Relationships that occur can be based on the order of color, shape, and size. According to researchers, the skill of sorting patterns can improve children's cognitive skills from an early age. According to the researcher, the number of children in group A whose abilities are still underdeveloped in sequencing activities according to the researcher needs to improve their skills using loose parts. This type of research is Classroom Action Research conducted in two cycles, each cycle consisting of three meetings. The subjects of this study were 10 boys and 10 girls in group A at Al Iman Kindergarten. The results of this study can be concluded that the skills of sorting patterns using loose part media or objects around the child have shown an increase, from cycle 1 to cycle 2. According to the researcher, cycle 2 was considered successful because it had completed undeveloped children. children who develop according to expectations in the order of living patterns of 15% of the entire population and increase the very well developed category to 85%. Keywords: Cognitive, Pattern Sorting Skill, Loose Part.